BEHAVIORAL EVIDENCE OF ANTIDEPRESSANT-LIKE ACTIVITY OF RAPHANUS SATIVUS L. VAR. CAUDATUS IN MICE - Younus, Ishrat; Siddiq, Afshan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Currently-available antidepressant agents produce various adverse effects, and are expensive. At present,various plants are being evaluated for their possible role against numerous diseases, and no doubt, the role of traditionaland complementary medicines in the development of effective therapy is incredible. The present study was designed toevaluate antidepressant-like activity of Raphanus sativus L. Var. caudatus at different doses in mice.Materials and Methods: Antidepressant potential of ethanolic extract of Raphanus caudatus L. was evaluated at threedifferent doses 250 mg/kg, 500 mg/kg and 1000 mg/kg by using forced swim test and tail suspension test on albinomale mice. The results were compared with control and standard mice groups administered with normal saline andFluoxetine respectively. In both parameters immobility period was recorded two times during 60 days dosing.Results: The ethanol extract at all three tested doses (250 mg/kg, 500 mg/kg and 1000 mg /kg) and standard fluoxetinedemonstrated notable antidepressant-like activity (p<0.05) in both FST and TST paradigms.Conclusion: Our results clearly show that Raphanus caudatus ameliorate depression-like behavior in rodent model,and can be used to establish newer antidepressant approaches in future. However, mechanism-based studies are neededto establish the mechanistic action of Raphanus caudatus L.